2006
DOI: 10.1002/art.22075
|View full text |Cite
|
Sign up to set email alerts
|

Oral salmon calcitonin reduces Lequesne's algofunctional index scores and decreases urinary and serum levels of biomarkers of joint metabolism in knee osteoarthritis

Abstract: Objective. To evaluate the effects of oral salmon calcitonin (sCT) on Lequesne's algofunctional index scores and on biomarkers of joint metabolism in knee osteoarthritis.Methods. In this randomized, double-blind trial, patients received either placebo (n ‫؍‬ 18), 0.5 mg of sCT (n ‫؍‬ 17), or 1 mg of sCT (n ‫؍‬ 18) daily for 84 days. Results. A total of 41 patients completed the study (13 in the group receiving 0.5 mg of sCT and 14 in each of the other 2 other groups). Although, on day 84, patients in both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(83 citation statements)
references
References 11 publications
1
80
1
1
Order By: Relevance
“…A few of these studies have also investigated the radiographic severity of OA and serum or urinary biochemical markers (18)(19)(20)(21)(22)(23). In the present study, we analyzed the largest panel of biochemical markers ever investigated in a wellcharacterized cohort of patients with knee OA and we observed that 14 of them were significantly associated with at least 1 imaging feature.…”
Section: Discussionmentioning
confidence: 71%
“…A few of these studies have also investigated the radiographic severity of OA and serum or urinary biochemical markers (18)(19)(20)(21)(22)(23). In the present study, we analyzed the largest panel of biochemical markers ever investigated in a wellcharacterized cohort of patients with knee OA and we observed that 14 of them were significantly associated with at least 1 imaging feature.…”
Section: Discussionmentioning
confidence: 71%
“…Studies in the ACL dog model [144,145] also showed that subcutaneous injections of calcitonin under therapeutic conditions reduced the progression of OA cartilage and subchondral bone changes as well as the level of serum markers of bone resorption up to 4 months after the surgery. A small phase II trial assessing the efficacy of oral salmon calcitonin in knee OA was recently published [146]. Results showed an improvement in function scores as well as a reduction in some biomarker levels.…”
Section: Drugs/agents That Target Bone Remodellingmentioning
confidence: 99%
“…The serum levels of C2C/Cpropeptide of type II collagen, which indicate the ratio of type II collagen degradation to synthesis, are also elevated in OA-susceptible compared with OA-resistant guinea pigs (24). In humans, calcitonin has been shown to reduce the serum levels of C2C and alleviate OA symptoms (25). Furthermore, positive correlations have been found between the MRI T2 parameter and serum levels of C2C in OA knees (26).…”
mentioning
confidence: 99%